The Influence of Transformational Leadership, Emotional Intelligence on Innovative Performance Behaviour Mediated by Knowledge Sharing in Employee Working in Digital Sector - Wijaya, Andreas; Tannia, Tannia; Andrian, Rendy; Vanessa Keylita Sutarna; Antariksa Christi, Yudiar; Novita, Novita (Dinasti Publisher, 2024)
This study investigates the pivotal role of innovative performance behavior among employees in the digital sector, focusing on how Emotional Intelligence and Transformational Leadership, influence Knowledge Sharing and Innovative Performance. As the digital market faces evolving technological challenges and heightened competition, companies must adapt to remain competitive. Data will be gathered through purposive sampling of 185 digital industry employees with a minimum of five years of experience. Using Google Forms, participants will respond to 19 questions on a 5-point Likert scale. Data analysis will be conducted using SMARTPLS. The findings highlight the critical impact of Emotional Intelligence and Transformational Leadership on Knowledge Sharing and Innovative Performance. High Emotional Intelligence, characterized by self-awareness, self-regulation, motivation, empathy, and social skills, enhances creativity, problem-solving, and adaptability, fostering a conducive environment for innovation. Employees with high Emotional Intelligence engage more in Knowledge Sharing behaviors, promoting better communication and collaboration. Transformational leaders drive innovation by inspiring and motivating their teams, encouraging creativity and risk-taking, and fostering a supportive environment. The study concludes that developing Emotional Intelligence and Transformational Leadership in organizations can significantly enhance Knowledge Sharing and Innovative Performance, leading to sustained innovation and competitiveness in the digital sector.